Recepcja prozy Warłama Szałamowa. Próba systematyzacji - Kulikowska, Małgorzata (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
The topic of this article is the reception of Varlam Shalamov’s output since his first official publication of The Kolyma tales in1978 inLondon until now. Works published inRussia andPoland, also inFrance,Great Britain,Italy,Israel,Germany,USA andAustralia have been deeply analysed. It was proved that first publications were dedicated to Varlam Shalamov’s biography and the portrayal of the Gulag civilization (since the second half of 90’s, last century). Problems of poetic in works are dominating in last publications. Apart of this, on the bases of thematics of chosen research papers in the article, some directions of further development of Shalamov’s legacy were determined.